Predictor for Ureteral Stent Removal in Gynecological Cancer Patients with a Ureteral Obstruction - Sung Hyun Ji; Young Kwon Hong; Young Dong Yu; Seung-Ryeol Lee (Urogenital Tract Infection)
Purpose This study investigated the possibility of ureteral stent removal in patients with gynecological cancer and ureteral obstruction. Materials and Methods From February 2010 to March 2022, the records of 121 patients with gynecological cancer and ureteral obstruction undergoing periodic ureteral stent replacement were reviewed retrospectively. Ureteral stent removal was attempted in patients who showed improvement in hydronephrosis on abdominal computed tomography (CT) after ureteral stent insertion and who lost symptoms. Success was defined as not having to reinsert the stent because there were no uncomfortable symptoms. The following were evaluated as predictors for ureteral stent removal: pre-removal serum creatinine, hypertension, diabetes, asymptomatic bacteriuria, type of gynecologic malignancy, prior radiotherapy, hydronephrosis laterality, obstruction level, hydronephrosis etiology, ureteral stent size, and ureteral stent duration. The hydronephrosis changes on abdominal CT were also evaluated. Results Among 121 patients, 74 with 81 obstructed ureters were evaluated. Of the 81 ureters, successful removal occurred in 30 (37.0%). There were significant differences between the success and failure cases regarding asymptomatic bacteriuria, prior radiotherapy, and hydronephrosis etiology. Logistic regression analysis showed that asymptomatic bacteriuria and hydronephrosis etiology were significant predictors of ureteral stent removal (p<0.05). There were also significant differences in the hydronephrosis changes depending on asymptomatic bacteriuria and hydronephrosis etiology (p<0.05). Conclusions In patients with gynecological cancer who have a ureteral stent in place due to ureteral obstruction, ureteral stent removal may be considered in patients who do not have asymptomatic bacteriuria or other etiologies, such as external ureteral pressure or ureteral cancer metastasis.